Observed rapid adjustment of the atmospheric boundary layer to submesoscale sea surface temperature fronts - Igor Uchoa; Jacob O. Wenegrat; Alex Kinsella; Inés M. Leyba; Larry W. O’Neill; Luc Lenain (Proceedings of the National Academy of Sciences, 2026)
Current understanding of the role of ocean variability in air–sea exchange is constrained to large and mesoscale dynamics. Oceanic fronts and filaments with horizontal spatial scales of order 0.1 to 10 km—denoted submesoscale—are challenging to observe due to their fast-evolving flow and small spatiotemporal scales of variability. Observations investigating the air–sea fluxes at the submesoscale have shown substantial fluxes of heat, moisture, and momentum, affecting the structure of the overlying atmosphere. Here, modulations of the turbulent atmospheric boundary layer driven by ocean temperature anomalies are investigated using submesoscale-resolving ship and airborne measurements, providing in situ evidence of the atmospheric response to ocean submesoscale temperature variability. Observations suggest near-surface turbulent mixing driven by strong air–sea fluxes of heat and momentum, modifying the vertical structure of the planetary boundary layer. Linear regression coefficients between wind speed and sea surface temperature anomalies reveal a response similar in magnitude to that seen at larger scales, with an integrated change of 0.23 m s −1 °C −1 , but occurring over smaller length-scales, implying sharper gradients. Lagged correlations and scaling analysis imply a combined influence of horizontal advection and vertical turbulent mixing of momentum in the atmosphere, previously only described by numerical simulations. Observed cross-frontal wind divergences over the lower 200 m suggest coherent circulations with vertical velocities of order 1 cm s −1 . These observations confirm the rapid adjustment of the marine boundary layer to submesoscale ocean temperature variability and the importance of submesoscale-driven air–sea fluxes in changing the properties of the lower atmosphere, processes not resolved in most forecasting and prediction models.